I testimoni e lo storico. Jerzy Grotowski: tradizione, eredità, trasmissione (appunti e provocazioni in occasione dell'anno grotowskiano) (Mantichora. Italian Journal of Performance Studies, 2020)
Grotowski has created one of the few living traditions in the contemporary theater. This essay, conceived during the grotowskian year (2009), reflects on the paradoxical aspects of the grotowskian tradition, and on its originality in comparison with those resulted from others masters of the Twentieth century theater. It poses a methodological problem, crucial for the future grotowskian studies, that will be possible with the contribution of the ‘actors’ operating for the transmission of Grotowski’s work